USE OF FOLK ORAL CREATIVITY TO ELIMINATE SPEECH DEFECTS - Makhmudova Oygul Tokhirjonovna (Bright Mind Publishing, 2025)
Life is such that everything is connected with time and era. Whether it's oral folk art or literary works created by writers, they all serve their time and era. People live by reading poetic works, understanding whether their life path is right or wrong, relying on them, drawing conclusions, rejoicing in achievements, and suffering from shortcomings. This is more noticeable in the younger generation. The most ancient examples of Central Asian peoples' folklore are preserved only in some historical monuments, scientific works, and memoirs. The oldest folklore works consist of myths, legends of the battle genre, heroic epics, songs, and proverbs.
Keywords: Oral folk literature, tongue twister, proverb, riddle, folktale, literary genres, speech disorders, speech development.